UJI BIOAKTIVITAS EKSTRAK BUAH SAWO MANILA (Manilkara zapota) TERHADAP PERTUMBUHAN BAKTERI Salmonella typhi - Subakhir Salnus; Nurhamsia (Jurnal Kesehatan Panrita Husada, 2019)
This research was conducted bioactivities by using raw fruits of sapodilla sapota (Manilkara zapota) as a drag growth media of Salmonella typhi bacteria causes typhoid fever disease. Salmonella typhi is a species of bacteria that are gram-negative bacilli shaped, facultative, aerobic, moving with a single pertrich. Sapdilla sapota has antimicrobial activity against Salmonella typhi, because it contains a variety of secondary metabolite compounds such as saponins, tannins and flavonoids. The purpose of this research was to know how efective the raw fruits of sapodilla sapota (Manilkara zapota) against the growth of Salmonella typhi. This is an laboratory research by using diffusion test method. The sample of this research is to extract the fruit of sapodilla sapota (Manilkara zapota) crude. The results of this research, are 35% concentration of extract cannot be formed drag zone (0 mm), but in 40, 45, 50 and 55% of concentration there are had drag zone (9 mm, 13 mm, 13.5 mm, and 18 mm). this can be said that the raw fruit of sapodilla sapota extract can inhibit the growth of Salmonella typhi bacteria can be done, then the next extension to the sufferers of the disease typhus to consume raw fruits of sapodilla sapota so that can reduce the growth of bacteria.